South Polar chart / from various authorities with amendments and additions to 1937 (Great Britain. Hydrographic Office, 1938)
New editions 20th May 1938 Relief shown by spot heights and hachures. Depths shown by soundings.; "Crown copyright reserved."; "Engraved 1926."; "328.38" -- upper right margin.; "Zc 1938" -- lower right margin. Color;